2010
DOI: 10.1177/1528083710371488
|View full text |Cite
|
Sign up to set email alerts
|

Low Temperature Plasma/Metal Salts Treatments for Improving Some Properties of Polyamide 6 Fibers

Abstract: The effect of plasma treatments with oxygen and argon gases on some properties of polyamide 6 fibers is thoroughly investigated. The treated fabric with oxygen plasma is further treated with some metal salts solutions such as copper sulfate, nickel sulfate, and silver nitrate to study their effect on the antibacterial properties of polyamide fibers. The changes induced in roughness, wettability, and dyeability of polyamide 6 fabric are given. The surface morphology of treated fabric is characterized by using s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 22 publications
0
10
0
3
Order By: Relevance
“…It may result in desirable surface modifications (about 10 nm in depth), including but not limited to surface etching, activation, crosslinking, chain scission, decrystallisation, and oxidation . Atmospheric pressure plasma techniques are gaining popularity owing to the ease of incorporating them in textile finishing operations .…”
Section: Introductionmentioning
confidence: 66%
See 3 more Smart Citations
“…It may result in desirable surface modifications (about 10 nm in depth), including but not limited to surface etching, activation, crosslinking, chain scission, decrystallisation, and oxidation . Atmospheric pressure plasma techniques are gaining popularity owing to the ease of incorporating them in textile finishing operations .…”
Section: Introductionmentioning
confidence: 66%
“…Plasma‐treated samples showed better water absorption than untreated samples, even after 48 h of storage. This may be due to the formation of hydrophilic chemical groups (–COOH, –OH, –C=O) on the surface of the plasma‐treated samples, as shown by ATR‐FTIR analysis, and the induced changes in fibre morphology, as indicated by the SEM micrographs and reported elsewhere . Previous studies indicated that surface modifications by low‐temperature plasma are not permanent and progressively vary, depending on the storage conditions of the sample.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A schematic drawing of the experimental arrangement is depicted elsewhere (Raslan et al 2010).Wool/polyester blend fabric was exposed to DBD by using different gases, such as oxygen, nitrogen and air, at different discharge powers (1-3 watts) for different time intervals (1-12 min).…”
Section: Plasma Treatmentmentioning
confidence: 99%